Advanced-ignition-concept exploration on OMEGA - Theobald, W; Anderson, K; Betti, R; Craxton, R; Delettrez, J; Frenje, J; Glebov, V; Gotchev, O; Kelly, J; Li, C; MacKinnon, A; Marshall, F; et al. (2009)
Advanced ignition concepts, such as fast ignition and shock ignition, are being investigated at the Omega Laser Facility. Integrated fast-ignition experiments with room-temperature re-entrant cone targets have begun, using 18 kJ of 351 nm drive energy to implode empty 40 νm thick CD shells, followed by 1.0 kJ of 1053 nm wavelength, short-pulse energy. Short pulses of 10 ps width have irradiated the inside of a hollow gold re-entrant cone at the time of peak compression. A threefold increase in the time-integrated, 2 to 7 keV x-ray emission was observed with x-ray pinhole cameras, indicating that energy is coupled from the short-pulse laser into the core by fast electrons. In shock-ignition experiments, spherical plastic-shell targets were compressed to high areal densities on a low adiabat, and a strong shock wave was sent into the converging, compressed capsule. In one experiment, 60 beams were used with an intensity spike at the end of the laser pulse, and the implosion performance was studied through neutron-yield and areal-density measurements. In a second experiment, the 60 OMEGA beams were split into a 40+20 configuration, with 40 low-intensity beams used for fuel assembly and 20 delayed beams with a short, high-intensity pulse shape (up to 1 × 1016 W cm-2) for shock generation. © 2009 IOP Publishing Ltd.